(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
The article presents material on the relevance of the fight against mites in the conditions of industrial poultry farming. Data on the biology of the development of the red chicken mite is covered; the optimal development conditions are a temperature of 23-25 0 C and a relative humidity of 60-80%. Diagnostic methods are briefly and accurately described. and the use of veterinary drugs to combat ticks, in the form of oral and external use.